Upper 40% requirement of R.A. 7164 and the performance of UNP BSN classes of 1998, 1999 and 2000 - Ulibas, Elmer T. (2001)
Realizing the need to undertake research - based documentation of the merits of the upper 40% requirement of the Philippine Nursing Act of 1991 (R.A. 7164) for all applicants to the nursing program, the investigator was motivated to pursue this endeavor.{{{{This study determined the relationship of the upper 40% requirement of R.A. 7164 with the college academic achievement and Integrated Nursing Comprehensive Licensure Examination (INCLE) performance of the University of Northern Philippines - Institute of Nursing BSN Classes 0f 1998, 1999, and 2000.{{{{This study employed non-experimental research design specifically export facto design and utilized the documentary analysis procedure.{{{{Using the mean, Pearson r and t - test, the findigd showed that the implementation of the upper 40% requirement for the graduates of classes 1998 - 2000 of the University of Northern Philippines resulted to a good college academic achievement and a better nursing board examination performance than graduates of classes 1995 - 1997 when said requirement was not yet implemented. The results of this study supported the justification for the continued implementation of the upper 40% requirement as a general entrance requirement for applicants to the nursing program of the University of Northern Philippines.{{{{The recommendations of the study stressed on the continuity of implementation of requiring applicants to the nursing program of the University of Northern Philippines Institute for the submission of certifications that they belong to the upper 40% of their graduating class in high school. Emphasis was also given on the undertaking of studies similar to this study to other colleges of nursing and with wider setting coverage to have more research - based documentations on the justification of the upper 40% requirement of R.A. 7164.
Thesis (Master of Arts in Nursing) -- University of the Philippines Manila
Keywords: Academic achievement; Education, Nursing; School admissions